2011
DOI: 10.1016/j.ejso.2010.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Role of MRI (magnetic resonance imaging) versus conventional imaging for breast cancer presurgical staging in young women or with dense breast

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. The role of magnetic resonance imaging (MRI) in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 29 publications
(48 reference statements)
1
38
0
Order By: Relevance
“…The high soft tissue resolution of an MRI and the advantages of enhancement scanning show the full appearance of ductal carcinoma in situ (DCIS) as well as the conditions of multicentricity and sub-lesions to determine the scope of tumors more accurately (16). MRI can detect breast cancer lesions as detected by ultrasound, and can detect multicentricity, invasive mammary carcinoma and contralateral breast cancers in order to guide the physicians on planning the therapeutic schedule (17). The present study showed that according to the inter-group comparisons age, tumor distribution and T-staging were not significantly different among the groups.…”
Section: Discussionmentioning
confidence: 99%
“…The high soft tissue resolution of an MRI and the advantages of enhancement scanning show the full appearance of ductal carcinoma in situ (DCIS) as well as the conditions of multicentricity and sub-lesions to determine the scope of tumors more accurately (16). MRI can detect breast cancer lesions as detected by ultrasound, and can detect multicentricity, invasive mammary carcinoma and contralateral breast cancers in order to guide the physicians on planning the therapeutic schedule (17). The present study showed that according to the inter-group comparisons age, tumor distribution and T-staging were not significantly different among the groups.…”
Section: Discussionmentioning
confidence: 99%
“…36 Recommending supplementary staging with an additional imaging tool such as MRI may be appropriate for patients with pure DCIS and dense breast tissue. 3739 …”
Section: Discussionmentioning
confidence: 99%
“…MRI displays high sensitivity for invasive breast cancer (including mammographically occult invasive breast cancer; ref. [31][32][33]; however, its use is limited, by its relatively low sensitivity in the detection of DCIS and low specificity for both invasive carcinoma and DCIS (34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%